1997
DOI: 10.1044/jslhr.4003.493
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Computer-Provided Reading Treatment for Chronic Aphasic Adults

Abstract: We examined the effects of computer-provided reading activities on language performance in chronic aphasic patients. Fifty-five aphasic adults were assigned randomly to one of three conditions: computer reading treatment, computer stimulation, or no treatment. Subjects in the computer groups used computer 3 hours each week for 26 weeks. Computer reading treatment software consisted of visual matching and reading comprehension tasks. Computer stimulation software consisted of nonverbal games and cognitive rehab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(112 citation statements)
references
References 25 publications
1
94
0
5
Order By: Relevance
“…In comparison with an untreated control group, one study by Hagen (1973) was excluded because of the lack of true randomization (the patients were sequentially assigned to treatment or no treatment). Another study (Katz and Wertz, 1997) was probably excluded because it dealt only with computer-assisted reading rehabilitation. Two small RCTs (class I) (Helffenstein and Wechsler, 1982;Thomas-Stonell et al, 1994), which reported positive treatment effects, were excluded from the Cochrane review because they were devoted to communication disorders after TBI.…”
Section: Rehabilitation Of Aphasiamentioning
confidence: 99%
“…In comparison with an untreated control group, one study by Hagen (1973) was excluded because of the lack of true randomization (the patients were sequentially assigned to treatment or no treatment). Another study (Katz and Wertz, 1997) was probably excluded because it dealt only with computer-assisted reading rehabilitation. Two small RCTs (class I) (Helffenstein and Wechsler, 1982;Thomas-Stonell et al, 1994), which reported positive treatment effects, were excluded from the Cochrane review because they were devoted to communication disorders after TBI.…”
Section: Rehabilitation Of Aphasiamentioning
confidence: 99%
“…[5][6][7] To date, most computer programs for people with aphasia focus on tasks at the single-word level including verbal and written word finding, single-word auditory comprehension skills, and single-word visual recognition and reading comprehension. 3,[8][9][10][11][12][13] We have recently demonstrated the feasibility of a computer program incorporating conversational practice. 14 AphasiaScripts™ provides a more realistic conversational context for practicing language skills than working on single-word tasks.…”
mentioning
confidence: 99%
“…Surveyed clinicians primarily used cognitive-communication assessments of reading, whereas the studies in the review used assessments from the fields of aphasia, education and neuropsychology. Both survey participants and the research literature 89 identified that outcome measures for reading were often not sensitive in identifying functional changes. The importance of using informal / other measures to assess reading in pwABI was identified in both the systematic review and the clinical survey.…”
Section: Assessment Measuresmentioning
confidence: 99%